2008 global crisis: Is foreign currency denominated debt an important indicator? - Ozden Akca (University of California, Santa Cruz Institute for International Economics (SCIIE), 2011)
Foreign currency denominated debt as an influence of exchange rate pressure during the 2008 global crisis is explored across 58 countries. Countries with higher ratios of foreign currency denominated debt to total international debt experienced significant currency depreciation during the global crisis. Predicted values of foreign currency denominated indebtedness are obtained based on country characteristics by employing a double censored tobit model estimation technique. Comparison of actual to predicted values just prior to the crisis demonstrates whether or not countries are over-indebted. According to our analysis, over-indebted countries experienced higher rates of exchange rate depreciation in the global crisis of 2008. Additionally, oil exporters, countries with strong financial linkages with the US and net importers experienced significant depreciation. International reserve accumulation before the crisis is associated with currency appreciation during the crisis. However, this result is insignificantly estimated.
Keywords: F31; F34; F41; G10; G15; 330; 2008 Global Crisis; Exchange Rate Pressure; Foreign Currency Denominated Debt; Over-indebtedness; Double Censored Tobit Model